The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00415-018-8946-0
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic function testing in Friedreich’s ataxia

Abstract: BackgroundFriedreich ataxia (FRDA) is an inherited movement disorder which manifests with progressive gait instability, sensory loss and cardiomyopathy. Peripheral neuropathy is an established feature of FRDA. At neuropathological examination, a depletion of large, myelinated axons is evident, but also unmyelinated fibers are affected which may result in a variety of sensory and autonomic signs and symptoms. Impaired temperature perception, vasomotor disturbances of lower extremities and a high prevalence of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…and Takazaki et al . found similar results in a closely related heredodegenerative disorder – Friedreich's ataxia – and also considered deconditioning as a reasonable explanation .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…and Takazaki et al . found similar results in a closely related heredodegenerative disorder – Friedreich's ataxia – and also considered deconditioning as a reasonable explanation .…”
Section: Discussionsupporting
confidence: 66%
“…Our belief is that this is not a true sign of autonomic failure, but instead may be related to poor physical conditioning due to motor handicap. Indelicato et al and Takazaki et al found similar results in a closely related heredodegenerative disorder -Friedreich's ataxiaand also considered deconditioning as a reasonable explanation [23,24]. The QSART is a well validated test to assess sympathetic sudomotor functioning [25].…”
Section: Discussionmentioning
confidence: 74%
“… 79 Increased heart rate at rest and during orthostatic challenge is the most common autonomic abnormality in FRDA patients. 80 Cardiovascular dysfunction, however, is primarily due to heart disease rather than dysautonomia.…”
Section: Affected Systems In Frdamentioning
confidence: 99%
“…5,10,13,14,18 Cardiovascular dysautonomia is very rare, 28 but some patients may show tachycardia at rest and during orthostatic challenge. 29,30 Early markers of myocardial dysfunction in cases with normal left ventricular ejection fraction include reduced longitudinal myocardial strain on echocardiography 31 and signs of cardiac remodeling on cardiovascular magnetic resonance. 32,33 Patients with progressive declining left ventricular ejection fraction, usually below 55%, have worse outcome.…”
Section: Frda (Or Atx-fxn)mentioning
confidence: 99%